THE INFLUENCE OF TEACHING CREATIVITY ON STUDENT LEARNING EFFECTIVENESS AT MTS - Solihin, Mohammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The teacher is a person who conveys the mandate of knowledge as well as educates and is responsible for the personal formation of students. The teacher is also a teacher, who is required to be a professional and creative teacher in teaching, therefore the teacher must have creativity to uphold professional values in his work as a teaching staff. The formulation of the problem in this research is "Is there any influence of teacher's teaching creativity on the effectiveness of student learning at MTs Al-Husna" and "How much influence does teacher's teaching creativity have on the effectiveness of student learning at MTs Al-Husna". This study aims to "To find out whether there is an influence of teacher's teaching creativity on the effectiveness of student learning at MTs Al-Husna" and "To find out how much influence teacher's teaching creativity has on the effectiveness of student learning at MTs Al-Husna". The hypothesis that the researchers put forward is (Ho) there is no positive and significant influence between the influence of teacher's teaching creativity on the effectiveness of student learning and (Ha) there is a positive and significant influence of teacher's teaching creativity on the effectiveness of student learning. The method used in this research is a questionnaire method, observation, and also documentation. From the results of the correlation analysis, it turns out that there is an influence between the teacher's teaching creativity on the effectiveness of student learning. With this data analysis is continued with simple linear regression testing to find out how much influence the teacher's teaching creativity has on the effectiveness of student learning. The regression equation used to predict teacher teaching creativity based on student learning effectiveness is Y' = 19.6209+7.04316 X. This means that if teacher teaching creativity is increased to a value of 36, student learning effectiveness will be 26.66407 or 26.667%. And the value of R = 0.36%, indicating that 0.36% of the effectiveness of student learning is influenced by the teacher's teaching creativity.